On the Consistency Coefficient of a Power-Law Flow of Blood Through the Narrow Vessel - Mazumdar, H.P.; Habishayasi, U.N.; Ghorai, S.; Roy, B.C. (Engineering Transactions, 1995)
In this paper, we study the behaviour of the relative consistency coefficient of an assumed power-law flow of blood through the narrow vessel. The flow field comprises two layers, e.g. a marginal plasma layer near the wall and a core layer which is suspension of red cells in plasma. The relative consistency coefficient is determined by equating the sum of volume rates of flow in the two layers to the volume rate of flow in case the two fluids are replaced by a single power-law fluid with an appropriate consistency coefficient. The results are displayed graphically and discussed.